Once upon a time in the East : the chronological and geographical distribution of terra sigillata and red slip ware in the Roman East - Bes, Philip, (Roman and late antique Mediterranean pottery ;, 2015)
Philip Bes summarises the results of his PhD thesis (Catholic University of Leuven) on the analysis of production trends and complex, quantified distribution patterns of the principal traded sigillatas and slipped table wares in the Roman East, from the early Empire to Late Antiquity. He draws on his own work in Sagalassos and Boeotia, as well as an exhaustive review of archaeological publications of ceramic data. The analysis compares major regional blocks, documenting coastal as well as inland sites, and offers an interpretation of these complex data in terms of the economy and possible distribution mechanisms.